Remittances and Credit Markets: Evidence from Senegal - Linguère Mously Mbaye (Institute for the Study of Labor (IZA), 2015)
This study investigates the impact of remittances on credit markets in Senegal. The findings show that remittances and credit markets are complements; namely, the receipt of remittances increases the likelihood of having a loan in a household. This result is robust after controlling for the potential endogeneity of remittances through household fixed effects and an instrumental variable approach. A detailed analysis also shows that the impact of remittances on credit markets is mainly driven by loans taken for consumption and food, in particular, as well as loans provided by informal institutions.
Keywords: F24; O15; O16; 330; migration; remittances; credit markets